2016
DOI: 10.1162/artl_a_00194
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Newtonian Fluid Robot

Abstract: New types of robots inspired by biological principles of assembly, locomotion, and behavior have been recently described. In this work we explored the concept of robots that are based on more fundamental physical phenomena, such as fluid dynamics, and their potential capabilities. We report a robot made entirely of non-Newtonian fluid, driven by shear strains created by spatial patterns of audio waves. We demonstrate various robotic primitives such as locomotion and transport of metallic loads-up to 6-fold hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Indeed, an eigenvector analysis on all the β*’s and β’s studied here showed that only a single non-negative eigenvector exists for each. It is tempting to consider an eigenvector with all non-negative elements as representing a molecular composition (as sometimes done [ 39 , 77 , 79 ]), homologue to a compotype. A vector with some negative elements, representing negative molecular counts or concentrations, by definition cannot represent molecular composition.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, an eigenvector analysis on all the β*’s and β’s studied here showed that only a single non-negative eigenvector exists for each. It is tempting to consider an eigenvector with all non-negative elements as representing a molecular composition (as sometimes done [ 39 , 77 , 79 ]), homologue to a compotype. A vector with some negative elements, representing negative molecular counts or concentrations, by definition cannot represent molecular composition.…”
Section: Resultsmentioning
confidence: 99%
“…Motion in a non‐Newtonian liquid robot was also demonstrated using an array of acoustic transducers, producing controllable movements, and also the capability of carrying a load …”
Section: System Functionalitiesmentioning
confidence: 99%
“…In the past two decades, robots have been widely used in various fields including monitoring, industrial automation production, visual navigation, automatic image interpretation, human–computer interaction and virtual reality [1]. Machine vision is to simulate the visual function of human eyes using computers, whose objective is to extract information from images or image sequences and then perform morphological and motion recognition for three‐dimensional (3D) scenes and objects in the real world [2–4].…”
Section: Introductionmentioning
confidence: 99%